Kelayakan tepung darah dalam pembuatan pakan untuk pertumbuhan ikan nila, Oreochromis niloticus) - Takou, Putri D.; Mokolensang, Jeffrie F.; Pangkey, Hanneke; Lumenta, Cyska; Manoppo, Henky; Wantasen, Adnan S. (e-Journal BUDIDAYA PERAIRAN, 2021)
The purpose of this study was to determine the feasibility of blood meal in various level inclusins in promoting the growth rate and nutrient utilization of O. niloticus. The results showed that the absolute growth of tilapia in treatment 2 (with a combination of 20%) was higher than the other treatments. The daily growth rate of tilapia in treatment 2 (3.5% / day) was higher than other treatments. Likewise, with the feed change value, treatment 2 showed significantly different from other treatments. The combination of tuna fish meal waste and blood meal showed significantly different results from the results of statistical tests